The acceptability of COVID-19 vaccination during spring crisis in Myanmar - Aung, Yadanar; Htun, Zaw Z.; Marzo, Roy R. (International Journal Of Community Medicine And Public Health, 2021)
Background: During the spring crisis, the coup and COVID-19 have led to a weakening vaccination program and Myanmar’s coronavirus prevention measures have been collapsed. The objective of this study was to determine the COVID-19 vaccine acceptance and assess its associated factors among the general adult population in Myanmar. Methods: A cross-sectional, web-based survey was conducted with a total of 301 participants. The association between vaccine acceptability and its determinants was assessed by binary logistic regression analysis. Results: The majority (90.4%) responded that they would like to accept vaccination if it is successfully developed and approved for listing in the future. Among the respondents, two-fifths (40.5%) had already received 1st dose of the COVID-19 vaccine, and 86.4% of the respondents thought that doctor’s recommendation is a crucial factor in vaccination decision-making, while 70.4% responded that vaccine price is an essential factor. If the younger age of participants who possessed lower monthly household income and agreed that the doctor’s recommendation is an important factor in vaccine decision making, the probability of accepting vaccine was more chance than those of older age participants. Conclusions: The study highlighted that majority of the respondents wanted to accept the vaccine although they were concerned about the side effects and political unrest. It is the recommended to develop a strategy successfully to strengthen vaccine convenience.